2005
DOI: 10.1007/bf02893056
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic role of the antibody response to the 38kDa, 16kDa proteins and lipoarabinomannan of mycobacterium tuberculosis

Abstract: The antibody response to the 38kDa, 16kDa and Lipoarabinomannnan (LAM) antigens of Mycobacterium tuberculosis was evaluated using three different ELISAs based on these antigens.The study group included tuberculosis patients (n=52), patients with HIV and TB co-infection (n=10), other chest symptomatics (n=5), HIV infected individuals (n=10), leprosy cases (n=7) and healthy controls (n=75). The results indicate that the 38kDa and LAM based ELISA for IgM/IgG has a low specificity (ranging from 69-85%) and sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…In search of rapid and cost-effective diagnosis of tuberculosis, serological test have been considered an attractive option. In recent past decades, a variety of serological assays have been developed such as latex agglutination, ELISA, indirect immunofluorescence and rapid immunochromatographic tests891011. The rapid serological tests have successfully been used to combat several infectious diseases like malaria, leishmaniasis, HIV, hepatitis viral infections etc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In search of rapid and cost-effective diagnosis of tuberculosis, serological test have been considered an attractive option. In recent past decades, a variety of serological assays have been developed such as latex agglutination, ELISA, indirect immunofluorescence and rapid immunochromatographic tests891011. The rapid serological tests have successfully been used to combat several infectious diseases like malaria, leishmaniasis, HIV, hepatitis viral infections etc.…”
Section: Discussionmentioning
confidence: 99%
“…To develope the serological tests, for the diagnosis of tuberculosis, researchers have used both crude as well recombinant antigens8912. The performance of these tests has been evaluated using single as well as cocktail of multiple antigens13141516.…”
Section: Discussionmentioning
confidence: 99%
“…In support of our findings, Song et al, 2017 demonstrated that HIV-infected patients in South Africa mounted a greater response to a panel of 8 antigens (Rv2853, Rv2031c, Rv0054, Rv0831c, Rv3405c, Rv3544c, Rv0222, Rv0948c), compared to HIV-uninfected patients, and vice-versa in patients from the United States of America. A higher sensitivity was reported amongst Indian HIV-TB co-infected patients compared to TB alone, for the detection of the 16kDa and 38kDa antigens (80% and 60% respectively, [18]) and PGL-Tb1 and ESAT-6/CFP10 (75.5% and 50.9% respectively, [19]). Similar results were reported for Antigen 85B [20].…”
Section: Resultsmentioning
confidence: 99%
“…detection of tuberculosis is significantly increased to 95.2%. Research also shows that the probability to specify every one of the three antigens is very high on a single TB patient and after effective treatment the probabilities would be very low [12]. This indicates that a single antigen detection test is of relatively low specificity and a combination of antigen detections may be needed to be of any value as a diagnostic test for TB.…”
Section: Resultsmentioning
confidence: 99%